Kontruksi Realitas Sosial Mengenai Perempuan Di Dalam Novel Cantik Itu Luka Karya Eka Kurniawan Dan Terjemahannya Beauty Is A Wound - Ilham, Ilham; Suratmoko, Bayu; Wahyudi, Jaemi; Noor Shaleh, Muhammad (Innovative: Journal Of Social Science Research, 2024)
This study explores the construction of social realities regarding women in Eka Kurniawan's novel "Cantik Itu Luka" and its translation "Beauty is a Wound" by Annie Tucker, using the Critical Discourse Analysis (CDA) approach of Sara Mills. The analysis reveals that language choices and translation techniques significantly impact gender representation. Changes in words and nuances in the translation can alter the original intensity and meaning, affecting readers' understanding of social and gender realities. This study emphasizes the importance of maintaining original nuances to convey social critique effectively and how language reconstructs social views on women in a patriarchal context